Socio-Cultural Construction of Recognition The Discursive Representation of Islam and Muslims in the British Christian News Media. - Faimau, Gabriel (Newcastle upon Tyne : Cambridge Scholars Publishing, 2013)
In recent years, extensive scholarly studies have been conducted on the representation of Islam and Muslims in the media. Despite the growing attention paid to the representations of Islam in the media, two important issues have been relatively neglected. Firstly, previous studies have focused on the mainstream (secular) media representations of Islam and Muslims. There has been no significant research or attention devoted to the discursive construction of Islam and Muslims in the British Chr...
Table of contents; preface; foreword; introduction; chapter one; chapter two; chapter three; chapter four; chapter five; chapter six; chapter seven; bibliography; list of internet websites
Description based upon print version of record.
Keywords: Journalism; Mass media; Muslims -- News media; Muslims -- Press coverage -- Great Britain; Islam -- Press coverage -- Great Britain; Mass media -- Religious aspects -- Christianity; Mass media in religion; Christianity and other religions -- Great Britain -- Islam; BUSINESS & ECONOMICS / Infrastructure; SOCIAL SCIENCE / General; Electronic books